The Cell Biology of Tau Secretion - Merezhko, Maria; Uronen, Riikka-Liisa; Huttunen, Henri J. (Frontiers in Molecular Neuroscience, 2020)
The progressive accumulation and spread of misfolded tau protein in the nervous system is the hallmark of tauopathies, progressive neurodegenerative diseases with only symptomatic treatment available. A growing body of evidence suggests that spreading of tau pathology can occur via cell-to-cell transfer involving secretion and internalization of pathological forms of tau protein followed by templated misfolding of normal tau in recipient cells. A number of studies have addressed the cell biological mechanisms of tau secretion. It now appears that instead of a single mechanism, cells can secrete tau via three coexisting pathways: (1) translocation through the plasma membrane, (2) membranous organelles-based secretion, and (3) ectosomal shedding. The relative importance of these pathways in secretion of normal and pathological tau is still illusive, though. Moreover, glial cells contribute to tau propagation and the involvement of different cell types as well as different secretion pathways complicates the understanding of tau pathogenicity. One of the important regulators of tau secretion is neuronal activity, but its mechanistic connection to tau secretion remains unclear and may involve all three secretory pathways of tau. This review summarizes the recent advancements in the field of tau secretion and discusses the role of neuronal activity in this process as well as a connection between glial cells and secreted neuronal tau.